2005
DOI: 10.4049/jimmunol.174.3.1374
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dendritic Cell Subsets: Differential Effects of Systemic TLR4 Stimulation on Migratory Fate and Activation In Vivo

Abstract: Dendritic cells (DC) present peripheral Ags to T cells in lymph nodes, but also influence their differentiation (tolerance/immunity, Th1/Th2). To investigate how peripheral conditions affect DC properties and might subsequently regulate T cell differentiation, we examined the effects of a potent DC-activating, TLR-4-mediated stimulus, LPS, on rat intestinal and hepatic DC in vivo. Steady-state rat intestinal and hepatic lymph DC are αE2 integrinhigh (CD103) and include two subsets, signal regulatory protein α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 48 publications
9
117
0
Order By: Relevance
“…Migrating DC comprise three subsets with different frequencies in intestinal and hepatic lymph DC migrating from the gut and liver in rats comprise two phenotypically distinct subsets differing in expression of CD172a and CD4 [9,10]. Here we have further analyzed these subsets following their collection from the thoracic ducts of MLNX and CoeLNX rats.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Migrating DC comprise three subsets with different frequencies in intestinal and hepatic lymph DC migrating from the gut and liver in rats comprise two phenotypically distinct subsets differing in expression of CD172a and CD4 [9,10]. Here we have further analyzed these subsets following their collection from the thoracic ducts of MLNX and CoeLNX rats.…”
Section: Resultsmentioning
confidence: 99%
“…For the intestine this is due to complete emptying of DC from the LP [9]. We have recently observed that feeding rats with R-848, a TLR7/8 ligand, also results in a dramatic but transient increase in the numbers of DC in intestinal and liver lymph ( [17] and unpublished observations).…”
Section: Oral R-848 Stimulates Differential Release Of Intestinal DCmentioning
confidence: 91%
See 2 more Smart Citations
“…In the intestinal epithelium, DC singe stand sample antigens passing through M cells or directly from within the intestine by opening tight junctions between IECs and extending dendrites into the gut lumen [46]. Microbial stimulation through TLRs controls DC activation, maturation, and migration at least in part through NF-κB and MAPK-dependent mechanisms [47][48][49]. Intestinal DCs may retain ingested live commensal bacteria within them, migrate to the mesenteric lymph nodes, and induce secretory IgA production without systemic immune activation [50].…”
Section: Discriminating Between Commensals and Pathogensmentioning
confidence: 99%